(untitled) (Polish Yearbook of International Law, 2023)
Following the so-called “special military operation”, which was in fact an open aggression against Ukraine, Russia was expelled from the Council of Europe. This step has significant legal consequences, including for the jurisdiction of the European Court of Human Rights. Meanwhile, many individual applications were filed with the Court, and Ukraine brought an inter-State complaint against Russia. Ukraine has also triggered the International Court of Justice. The Court has already ordered provisional measures. The ICC Prosecutor has launched an investigation into the most serious international crimes, war crimes, crimes against humanity, and genocide in Ukraine and delivered arrest warrants against the Russian President and his Commissioner for Children’s Rights. There is a serious discussion going on concerning the establishment of a special tribunal for the crime of aggression. This text deals with some aspects of the Russian “special military operation” cases before international courts. It attempts to identify what role the international courts may play in the new phase of the conflict in Ukraine and the extent and effect of their intervention, given the jurisdictional limitations and the inability to enforce judgments.